A Multicentre Molecular Analysis of Hepatitis B and Blood-Borne Virus Coinfections in Viet Nam - Dunford, Linda; Carr, Michael J.; Dean, Jonathan; Nguyen, Linh Thuy; Ta Thi, Thu Hong; Nguyen, Binh Thanh; Connell, Jeff; Coughlan, Suzie; Nguyen, Hien Tran; Hall, William W.; Thi, Lan Anh Nguyen (PLOS ONE, 2012)
Hepatitis B (HBV) infection is endemic in Viet Nam, with up to 8.4 million individuals estimated to be chronically infected. We describe results of a large, multicentre seroepidemiological and molecular study of the prevalence of HBV infection and blood-borne viral coinfections in Viet Nam. Individuals with varying risk factors for infection (n = 8654) were recruited from five centres; Ha Noi, Hai Phong, Da Nang, Khanh Hoa and Can Tho. A mean prevalence rate of 10.7% was observed and levels of HBsAg were significantly higher in injecting drug users (IDUs) (17.4%, n = 174/1000) and dialysis patients (14.3%, n = 82/575) than in lower-risk groups (9.4%; p<0.001). Coinfection with HIV was seen in 28% of HBV-infected IDUs (n = 49/174) and 15.2% of commercial sex workers (CSWs; n = 15/99). HCV infection was present in 89.8% of the HBV-HIV coinfected IDUs (n = 44/49) and 40% of HBV-HIV coinfected CSWs (n = 16/40). Anti-HDV was detected in 10.7% (n = 34/318) of HBsAg positive individuals. Phylogenetic analysis of HBV S gene (n = 187) showed a predominance of genotype B4 (82.6%); genotypes C1 (14.6%), B2 (2.7%) and C5 (0.5%) were also identified. The precore mutation G1896A was identified in 35% of all specimens, and was more frequently observed in genotype B (41%) than genotype C (3%; p<0.0001). In the immunodominant ‘a’ region of the surface gene, point mutations were identified in 31% (n = 58/187) of sequences, and 2.2% (n = 4/187) and 5.3% (n = 10/187) specimens contained the major vaccine escape mutations G145A/R and P120L/Q/S/T, respectively. 368 HBsAg positive individuals were genotyped for the IL28B SNP rs12979860 and no significant association between the IL28B SNP and clearance of HBsAg, HBV viral load or HBeAg was observed. This study confirms the high prevalence of HBV infection in Viet Nam and also highlights the significant levels of blood-borne virus coinfections, which have important implications for hepatitis-related morbidity and development of effective management strategies.